Perimesencephalic Subarachnoid Hemorrhage Is Not Always a Benign Condition: Hemorrhage Volume as a Predictor for Complications and Clinical Outcome - Emily Hoffmann; Công Duy Bùi; Alexandra Valls Chavarria; Michael Müther; Markus Holling; Manfred Musigmann; Max Masthoff; Mostafa Ergawy; Tobias D. Faizy; Christian Paul Stracke; Hermann Krähling; Burak Han Akkurt (Biomedicines)
Objective: The benign nature of perimesencephalic subarachnoid hemorrhage (pmSAH) can be challenged by the occurrence of complications. Given the limited prognostic value of established clinical parameters for the development of complications in patients with pmSAH, this study evaluates the potential of volumetric hemorrhage quantification for risk assessment and the evaluation of the clinical outcome. Material and Methods: In this retrospective single-center study, we analyzed all consecutive patients diagnosed with pmSAH between 2010 and 2023 at a tertiary care academic medical center in Germany. The volumetric quantification of the hemorrhage in cm3 was performed using non-contrast CT imaging. The occurrence of clinical complications, including hydrocephalus, vasospasm, and delayed cerebral ischemia (DCI), were assessed. Clinical outcomes were determined by the Glasgow Outcome Scale (GOS) at discharge. Multivariable logistic regression models were used to assess the correlation between quantified hemorrhage volumes and the occurrence of complications and clinical outcomes (GOS) controlled for other variables such as age, sex, cardiovascular risk factors, clinical symptoms, and the modified Fisher scale. Results: A total of 82 patients (58.5% male, 54.8 ± 12.1 years) were enrolled. The median World Federation of Neurosurgical Societies (WFNS) score for all patients at admission was 1.0 (IQR 1.0–1.0). During the clinical course, hydrocephalus occurred in 29%, vasospasm in 14.6%, and DCI in 8.5% of all patients. Hemorrhage volume quantification was found to be the strongest independent predictor for hydrocephalus (OR 1.28; 95% CI 1.02–1.61; p = 0.032) and vasospasm (OR 1.25; 95% CI 1.07–1.46; p = 0.007) and showed a high predictive accuracy in ROC analyses (AUC = 0.77 and 0.76, respectively). Conversely, neither clinical parameters nor the modified Fisher scale were associated with these complications. A higher hemorrhage volume was also significantly correlated with a worse functional outcome (GOS; β = –0.07, CI: −0.12–−0.02, p = 0.021). Conclusions: In patients with pmSAH, the volumetric quantification of hemorrhage may be an adequate prognostic parameter regarding the occurrence of hydrocephalus and vasospasm. In addition, the quantitative assessment of hemorrhage volumes was strongly associated with clinical outcomes in these patients. Despite the generally benign nature of pmSAH, this imaging biomarker could improve individualized clinical management strategies and inform about the risk for the occurrence of complications.